2013
DOI: 10.1080/02699931.2013.778818
|View full text |Cite
|
Sign up to set email alerts
|

I feel good, therefore I am real: Testing the causal influence of mood on state authenticity

Abstract: This manuscript has been accepted for publication at Cognition and Emotion. It has yet to go through editorial proofing and, as such, we ask that you do not quote text. The article may be cited however. RUNNING HEAD: Mood and State Authenticity 2 AbstractAlthough the literature has focused on individual differences in authenticity, recent findings suggest that authenticity is sensitive to context; that is, it is also a state. We extended this perspective by examining whether incidental affect influences authen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 75 publications
4
89
2
Order By: Relevance
“…Most investigations of state authenticity have taken place in the lab or relied on participants' retrospective reports, thus rendering it possible that the findings were not generalizable to real‐life situations (Kahneman et al, ). Notably, the present results largely confirmed those observed previously: State authenticity is correlated with positive mood (Lenton, Slabu et al, ; Turner & Billings, ), greater self‐esteem (Slabu et al, ), lower anxiety, and feeling ideal (Lenton, Bruder, et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most investigations of state authenticity have taken place in the lab or relied on participants' retrospective reports, thus rendering it possible that the findings were not generalizable to real‐life situations (Kahneman et al, ). Notably, the present results largely confirmed those observed previously: State authenticity is correlated with positive mood (Lenton, Slabu et al, ; Turner & Billings, ), greater self‐esteem (Slabu et al, ), lower anxiety, and feeling ideal (Lenton, Bruder, et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…by upbeat music) felt more authentic than participants put in a negative mood (e.g. by lugubrious music; Lenton, Slabu, et al, ). And as mentioned earlier, prior research in which participants were asked to recall a time when they felt either authentic or inauthentic indicated that experiences of authenticity are more closely associated with a sense of calm and approach‐related emotion clusters (e.g.…”
Section: What Is Authenticity?mentioning
confidence: 97%
“…Yet, one authenticity class (everyday) was associated with as much negative affect as one inauthenticity class (deflated). Thus, contrary to the implications of prior findings, the relation between negative affect and felt authenticity is not perfectly linear (Heppner et al, 2008; Lenton et al, 2013b). …”
Section: Discussioncontrasting
confidence: 98%
“…This definition stems from a dispositional view of authenticity, which has been the predominant narrative in the empirical literature to date. More recently, however, researchers have viewed authenticity through a situational or “state” lens (Heppner et al, 2008; Fleeson and Wilt, 2010; Gino et al, 2010; Lenton et al, 2013a,b). We concur with Fridhandler (1986) that “if a person is in a state he or she must be able to feel it” (p. 170).…”
Section: Introductionmentioning
confidence: 99%
“…This method provides an OLS-regression approach, using bootstrapping, for estimating the indirect effect, rather than judging this effect based on a series of null-hypothesis testing to infer full or partial mediation (for an example, see Lenton, Slabu, Sedikides and Power, 2013). In our study, this estimate should be interpreted as the indirect effect of being in a certain reward specificity condition on job pursuit intention, via personreward fit, relative to the mean.…”
Section: Resultsmentioning
confidence: 99%